Why Labor Supply Matters for Macroeconomics - Rogerson, Richard (Journal of Economic Perspectives, 2024)
Benchmark models taught in undergraduate macro do not attribute any role for labor supply as an important determinant of macroeconomic outcomes. The first part of this paper documents three facts. First, differences in hours of work across OECD economies are large and imply large differences in GDP per capita. Second, there are large differences in the size of tax and transfer programs across countries, as proxied by differences in government revenues relative to the GDP. Third, these two outcomes are strongly negatively correlated. Taken together, these facts suggest an important role for labor supply in affecting macroeconomic outcomes. I conjecture that the reason why macro textbooks do not include a discussion of labor supply stems from a belief that labor supply elasticities are sufficiently small that even large differences in work incentives do not generate important macroeconomic effects. The second part of this paper argues that this belief is based on incorrect inference linking small elasticities for prime age male to small aggregate labor supply elasticities. The role of labor supply at the extensive margin plays a critical role in understanding this mistake in this inference.
Keywords: Aggregate Human Capital; Aggregate Labor Productivity, Personal Income and Other Nonbusiness Taxes and Subsidies; includes inheritance and gift taxes, Welfare, Well-Being, and Poverty: Government Programs; Intergenerational Income Distribution; Wages; Unemployment